A Review on The Role of Nanoparticles in Modifying Mg Alloys and Composites - Amit Tiwari; Neeraj Kumar; Himanshu Vasnani; Sujeet Kumar Jha (International Journal of Fracture Mechanics and Damage Science, 2024)
Reviewing and assessing magnesium's uses in the automobile sector, which have the potential to greatly improve fuel efficiency and environmental preservation, is the goal of this study. The report provides an overview of magnesium alloys' present benefits, drawbacks, technological obstacles, and future prospects in the automobile sector. The development of magnesium matrix composites has advanced to a new level thanks to the magnesium matrix nanocomposites' exceptional mechanical qualities. Dispersing nanoparticles in metal melts is a challenging task, particularly in magnesium melts, which differ from other metal melts and pose a risk during the casting process. This indicates that it is very difficult to manufacture a magnesium matrix nanocomposite.Further, the magnesium matrix nanocomposites possess a distinctive characteristic in deformation behaviour, strengthening and toughening mechanism due to their special size effect of nanoparticles. As a result, the deformation behavior, mechanical characteristics, and strengthening and toughening procedures will be the main topics of this review. Future research ideas, development trends, and prospective applications of magnesium matrix nanocomposite are also explored.
Keywords: Magnesium matrix nanocomposite; Mechanical properties; microstructure; strengthening mechanism